John Bell's accounts on prince Alexander Bekovich-Cherkassky and his campaign to Khiva - Vladimir V. Yakovlev (Кавказология, 2024)
The article examines two accounts dedicated to the Khivan campaign of Prince Alexander Bekovich-Cherkassky, by the contemporary Scottish physician and diplomat John Bell. One of them was included in Bell’s book “Travels from St. Petersburg through Russia to Various Parts of Asia” (in Volume 1, containing the notes on the trip to Persia) published in 1763 and translated into Russian in 1776. Researchers have not widely known about the other account until now, as it is only contained in the unpublished (not even in English) manuscript entitled “Sundry Anecdotes of Peter the First,” preserved in the archives of the National Library of Scotland (Glasgow). Both texts are presented in the article in toto. The one from the travel book – in a new translation made especially for this article; the one from the collection of anecdotes about Peter the Great is published for the first time. A brief analysis is provided, involving documents and publications dedicated to this topic. The significance of these accounts lies in the fact that they belong to a person who was a contemporary to the event: J. Bell was in Persia when they occurred (it was there that the soldiers of Bekovich’s detachment who had escaped captivity managed to flee), and the majority of accounts of the event known in the literature were recorded and published half a century and more after the campaign.